Phagocytic Receptors Mediate Survival and Locomotor Resilience of Ethanol-Exposed Drosophila - Julia Citra Prastika; Sri Wahyuni M; Reski Amalia Rosa; Nadila Pratiwi Latada; Mukarram Mudjahid; Risfah Yulianty; Firzan Nainu (International Journal of Biomedical Science and Travel Medicine, 2025)
Background Ethanol is a widely studied toxicant known to induce oxidative stress and cellular damage across species. While phagocytic clearance is essential for maintaining tissue homeostasis, its role in protecting against ethanol-induced toxicity remains poorly understood. This study aims to elucidate the role of phagocytic receptors in modulating the organism’s response to ethanol-induced toxicity using Drosophila melanogaster. Methods To assess the functional significance of phagocytic receptors, we utilized behavioral locomotor assay and survival analysis on both wild-type and mutants deficient in the phagocytic receptors Draper and Integrin-[beta]v of Drosophila which are homologous to mammalian MEGF10 and integrins, respectively. Flies were exposed to the various concentration of ethanol, and their climbing ability and survival responses were compared across genotypes. Results Our results revealed that mutants lacking Draper and/or Integrin-[beta]v showed a significant reduction in locomotor activity (p < 0.05 to p < 0.0001) and an approximately two-fold decrease in survival time under ethanol exposure compared with wild-type flies. These findings indicate that impaired phagocytic clearance may exacerbate ethanol toxicity. Conclusion In summary, this study demonstrates that phagocytic receptors play a critical protective role against ethanol toxicity in D. melanogaster. The data suggest the interconnected roles of oxidative stress, apoptosis, and phagocytosis in maintaining tissue homeostasis, validating Drosophila as a robust model for investigating the effect of toxicant on the phenotypic features of metazoan species.